Importance of cooperation of preschool institution with family and community - Tarugashvili, Naira (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Effective work with children is impossible without partnership with families. The best results are determined by the convergence of family and kindergarten approaches and their coordinated action. A child develops in both environments, in the family and in the garden. He learns by examples, relationships. The child is a common interest, these two sides should complement and strengthen each other, mutual respect, open communication, consistent exchange of information, listening to each other, mutual understanding, learning from each other and cooperation serve the well-being of the child. The article reviews practical examples of family and community involvement in kindergarten life and examples of children's practical activities, which have a positive impact on the child's well-being, and give parents and the community more motivation to be more involved in kindergarten life.